The Teaching of Scienceand Cultural DiversityinMexico: a Studyin Secondary Basic Education - Lazos Ramírez, Luz (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2015)
In recent years, the objectives of intercultural education have been included in science subjects at all levels of the educational system of Mexico as part of the educational reforms to provide all students an education that allows them to use scientific and technological knowledge to better understand their problems and make decisions to solve them, recognizing the value of cultural diversity. This paper presents a diagnostic study of the conditions for science teaching and its relation to cultural diversity in Mexic. The objetive of this workis to contribute to the construction of theoretical and methodological proposals for intercultural science education, characterized by the recognition of social processes related to the generationof knowledge in social groups and the assessment of students as active agents of these processes. The results of the study in a secondary school basic education with a significant proportion of indigenous students, showed that the recognition of cultu-ral diversity in science education is almost imperceptible, despite the remarked objetives for inclusion that the official pro-grams have included. Some of the factors contributing to this situation are the lack of culturally relevant materials, the lack of training of teachers in the field of intercultural education and the lack of an intercultural perspective for incorporating the assessment of traditional knowledge and knowledge scientists in their epistemic and cultural dimensions. In the first section, a brief overview of trends in science education and its relation to cultural diversity, the second presents some characteristics of the educational system of Mexico relating to the establishment of science education as part of education intercultural, in the third section, a description and results of the diagnostic study in a school of basic secondary education in Mexico, finally, raise some lines of discussion for the construction of models and proposals for intercultural science education is presented.